Ultralow threshold polariton condensate in a monolayer semiconductor microcavity at room temperature - Zhao, Jiaxin (2021)
Exciton-polaritons, hybrid light–matter bosonic quasiparticles, can condense into a single quantum state, i.e., forming a polariton Bose–Einstein condensate (BEC), which represents a crucial step for the development of nanophotonic technology. Recently, atomically thin transition-metal dichalcogenides (TMDs) emerged as promising candidates for novel polaritonic devices. Although the formation of robust valley-polaritons has been realized up to room temperature, the demonstration of polariton lasing remains elusive. Herein, we report for the first time the realization of this important milestone in a TMD microcavity at room temperature. Continuous wave pumped polariton lasing is evidenced by the macroscopic occupation of the ground state, which undergoes a nonlinear increase of the emission along with the emergence of temporal coherence, the presence of an exciton fraction-controlled threshold and the buildup of linear polarization. Our work presents a critically important step toward exploiting nonlinear polariton–polariton interactions, as well as offering a new platform for thresholdless lasing.